USE OF FOUL LANGUAGE AND VIOLENCE IN WEB SERIES: AN ANALYTICAL STUDY (CAHIERS MAGELLANES-NS, 2024)
It is considered that whatever a person sees is what he thinks too. And what he thinks reflects in the way he talks. Thus, whatever a man watches or whatever he is shown is important. Slowly, the type of tendency which is imbibed by a person, also flourishes in the society. These days, OTT is emerging as a rapidly growing alternate for entertainment. It is defined as Over the Top Media Platform. It’s the means for entertainment that’s available easily on internet. Previously, cinema was considered to be the only means for entertainment. Before the emergence of cinema, drama, circus, etc. used to be the means for entertainment. Then, televisions came and then came the cable operators. These days, OTT is the best option for entertainment. Until a couple of days earlier, Netflix was the only OTT platform. Then came Voot, MX player, Disney Hotstar, Zee 5 and many more. Many more brands are entering this domain of OTT platforms.